1991
DOI: 10.1161/01.hyp.17.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of sodium-lithium countertransport and hypertension in Utah.

Abstract: A 7-year prospective study of a cohort of 1,458 normotensive adults from Utah pedigrees, screened from 1980 to 1985, was done to determine whether baseline levels of sodium-lithium countertransport were associated with an increased risk of future hypertension. Subsequent new hypertension (n = 39) was ascertained in 1989 from detailed follow-up medical questionnaires (67% response). Previous segregation analyses on a subset of these pedigree members who responded (n = 342) using family relationships in addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…8 Recently, however, there has been some controversy concerning the appropriateness of the method for determining the V max of NaLiCT across the red cell membrane. The method is based on the assumption that concentrations of external sodium approaching physiological levels are sufficient to saturate the external sodium binding sites, resulting in the transporter achieving its maximal turnover rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Recently, however, there has been some controversy concerning the appropriateness of the method for determining the V max of NaLiCT across the red cell membrane. The method is based on the assumption that concentrations of external sodium approaching physiological levels are sufficient to saturate the external sodium binding sites, resulting in the transporter achieving its maximal turnover rate.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] An increase in erythrocyte sodium-lithium countertransport (NaLiCT) activity is one of the most consistent alterations in membrane ion transport that have been demonstrated in essential hypertension. [7][8][9][10][11] Recently it was also shown that increased NaLiCT activity might be a predictor of subsequent hypertension. 12,13 It has also been suggested that increased NaLiCT activity might be a marker of genetic predisposition to hypertension, since NaLiCT activity has been reported to be increased in normotensive relatives of hypertensive individuals.…”
Section: Introductionmentioning
confidence: 99%
“…13 This familial nature is thought to be due to genetic factors as many studies, including that of identical twins, show that SLC activity is genetically inherited. 9,10,15 The level of lithium efflux was similar in the normotensive offspring of hypertensive parents to that of the already hypertensive group. However, it is worthy of note, that the level of intra-erythrocytic sodium was not elevated in the normotensive offspring of hypertensive parents over that of normotensive offspring of normotensive parents, unlike the case in hypertensive patients.…”
Section: Discussionmentioning
confidence: 74%
“…[3][4][5][6][7][8] There is now a body of evidence suggesting that sodium-lithium countertransport (SLC) abnormality in erythrocytes is associated with hypertension, as well as a predisposition to its development in Caucasians, 5,[9][10][11][12] that it aggregates in families 9,13,14 and that it is strongly influenced by genetic factors. 9,[13][14][15] Racial differences have been described in erythrocyte cation transport and it is thought that these changes are either reduced or may not occur in nonwhite persons, especially blacks. [16][17][18] However, Oforofuo et al 19 described an increased activity in a small group of Nigerian hypertensive patients but did not exclude the effects of drugs and also did not investigate the normotensive offspring of hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…17 In the Utah study, which included patients with familial combined hyperlipidaemia (FCH) and familial hypercholesterolaemia (FH), SLC activity also correlated strongly with blood pressure and lipids. 18,19 Both these epidemiological studies linked SLC to triglycerides, insulin resistance, and lipoprotein lipase activity as have studies in patients with type V hyperlipidaemia. 20 The Utah study population defined a subgroup of up to 10% of patients with essential hypertension who had a phenotype of dyslipidaemia allied with hypertension with a strong genetic component.…”
Section: Dietary Managementmentioning
confidence: 99%